Analisis Validitas Dan Reliabilitas Instrumen Penilaian Tengah Semester Bahasa Arab Keterampilan Menyimak Muhammadiyah Boarding School Ar Fachrudin Yogyakarta - Rahmawati, Alfi Rizqi; Moh. Mahbub; Siti Desi Hidayati (Institut Muslim Cendekia, 2025)
A good instrument test will show good data result. Measuring the result of this test uses the Validity and Reliability Test. Validity is measuring the extent to which measurements are carried out accurately, while reliabilty is measuring the extent to which measurements can be trusted because of their consistency. It can be said that Validity and reliability are interrelated. The aims of this research are: 1) to determine the validity of the mid-semester assessment questions for Arabic listening skills at MBS AR Fachrudin Yogyakarta; 2) to determine the reliability of the mid-semester assessment of arabic listening skills in the form of multiple choice question at MBS AR Fachrudin Yogyakarta. This research uses descriptive quantitative method with data collection techniques through mid-tests on the odd semester examination from a research sample of 30 students in class 10 L and 10 M for the 2023/2024 academic year. Validity and reliability analysis was carried out using SPSS 25 version. Based on the result of this study from 10 multiple choice questions items in the mid-semester assessment of Arabic listening skills at MBS AR Fachrudin in the validity test, it was found that 4 questions were classified as valid and 6 questions were invalid. Meanwhile, in the reliability test, the 4 valid questions were stated to have very low reliability.